Effect of Cockele Shells on Mortars Performance in Extreme Conditions - Abdelouahed, Assia; Hebhoub, Houria; Kherraf, Leila; Belachia, Mouloud (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper studies the use of cockle shell as supplementary cementitious materials SCMs as substitute for cement. The cockle shells generally have a high CaO content which can alter the behavior and the properties of mortars and concrete. Cockle shell is used with weight ratios of 5, 10, 15 and 20% to formulate a mortar with cockle shell and a control mortar CM with 0% of cockle shell.
Keywords: shells; cement; strength; properties; durability